Structured Collaborative Active Learning in Accounting Standards Instruction: Evidence from a Pre-Experimental Study - Septi Nurmalita; Dwi Handarini; Eka Septariana Puspa; Surya Anugrah; indy Permata Suyono; Rindi Lestari Suci Sofiyana (Journal of Creative Power and Ambition (JCPA), 2026)
This study investigates the effectiveness of the Card Exchange and Knowledge Tour, a structured collaborative active learning protocol, in improving conceptual understanding of Indonesian Financial Accounting Standards (PSAK) among undergraduate accounting students at a public university in Indonesia. Using a pre-experimental one-group pretest–posttest design involving 29 matched pairs, raw Google Form response data were independently cleaned, scored, and analyzed using paired-samples t-tests, Wilcoxon signed-rank tests, and effect size estimation, while proportion-correct metrics ensured comparability across a 12-item pre-test and an 18-item post-test. The findings indicate that students' scores improved significantly from 73.3% to 82.0% [t(28) = 2.924, p = .007; W = 63.5, p = .013], with a medium effect size (Cohen's d = 0.543; r = 0.460), exceeding typical benchmarks for single-session active learning interventions. Students also demonstrated significant improvements in learning confidence (p < .001) and perceived ability to apply accounting standards (p = .008), while the perception instruments exhibited strong internal consistency (α = .785–.862). Theoretically, the protocol simultaneously activates social constructivism, retrieval practice, and peer instruction, generating synergistic learning gains without requiring technological mediation. Practically, it provides accounting educators with an accessible, evidence-based alternative to technology-dependent instructional approaches, making it particularly suitable for institutions with limited digital infrastructure. The novelty of this study lies in integrating card-based learning, structured station rotation, and reciprocal peer questioning into a single theoretically grounded, multi-mechanism instructional protocol, an approach that has not previously been empirically examined in accounting standards instruction, particularly within the context of Indonesian PSAK education.